2(0.5x+7)-3(2.5x+8)=

Simple and best practice solution for 2(0.5x+7)-3(2.5x+8)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(0.5x+7)-3(2.5x+8)= equation:


Simplifying
2(0.5x + 7) + -3(2.5x + 8) = 0

Reorder the terms:
2(7 + 0.5x) + -3(2.5x + 8) = 0
(7 * 2 + 0.5x * 2) + -3(2.5x + 8) = 0
(14 + 1x) + -3(2.5x + 8) = 0

Reorder the terms:
14 + 1x + -3(8 + 2.5x) = 0
14 + 1x + (8 * -3 + 2.5x * -3) = 0
14 + 1x + (-24 + -7.5x) = 0

Reorder the terms:
14 + -24 + 1x + -7.5x = 0

Combine like terms: 14 + -24 = -10
-10 + 1x + -7.5x = 0

Combine like terms: 1x + -7.5x = -6.5x
-10 + -6.5x = 0

Solving
-10 + -6.5x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '10' to each side of the equation.
-10 + 10 + -6.5x = 0 + 10

Combine like terms: -10 + 10 = 0
0 + -6.5x = 0 + 10
-6.5x = 0 + 10

Combine like terms: 0 + 10 = 10
-6.5x = 10

Divide each side by '-6.5'.
x = -1.538461538

Simplifying
x = -1.538461538

See similar equations:

| -8x=5x-9 | | 9x^3+60x^2-21x=0 | | 2n+(2n+1.2)=4n+(2n+0.2) | | 9x^2+10x-2=0 | | (p-2)(p+4)+(p-2)(p+6)=0 | | 3/4c+3=12 | | 1+u=(-6) | | 2n+(2n+1.2)=4n+(2n+0.1) | | 5x+14-8x=16-19x+16x-2 | | -2.7x=10.2 | | [2r-6]=21 | | 35+35*0+1= | | 6+(x+2y)i=x+4i | | x-5=11-7x-56 | | 4=k-(-10) | | (r-2t)(r+2t)= | | 2x+4x=4(x+16) | | 0.5(x-6)=7 | | 6a^2+28a+16= | | 4(z+2)=3(z-4)+z | | 4-2(x+3)=8x-14 | | -4x+27=147 | | 0.25x+0.20(270-x)=56.75 | | -4x+27=127 | | 10xq=8.7475 | | 4(2+v)+35v=13v | | -40=2-4x-3x | | 18-(4m+3)=4+4m-13 | | 8=x+7-2 | | -7y+18=123 | | 15=3-(z+10) | | 8n+12=3n+18 |

Equations solver categories